Effects of Sodium Bicarbonate Mouthwash on Saliva pH and Oral Microflora - Pindobilowo; Dwi Ariani; Margaretha Herawati; Supraja Dwiyono; Ahn Byungchan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Introduction: Prevention of dental and oral disease is considered very important in maintaining daily dental and oral health. One way to prevent this is through sodium bicarbonate mouthwash. The aim of this study was to determine the effectiveness of sodium bicarbonate mouthwash in preventing dental caries. Methodology: using a narrative review method from several databases including Pubmed, Google Scholar, and the BMC Oral Health website. Conclusion : Mouthwash Sodium Bicarbonate is an effective cleaning agent, it can be used to remove stains on teeth, remove bad breath and can whiten teeth because this mouthwash can reduce bacterial growth and remove plaque buildup.